Stunting Among Wealthy Indonesian Families: A Cross-Sectional Study of Children Under the Age of Two - Laksono, Agung Dwi; Wulandari, Ratna Dwi; Susianti, Novia; Samsudin, Mohamad; Musoddaq, Muhamad Arif (Journal of Population and Social Studies [JPSS], 2024)
Previous studies globally report that poverty was a determinant of stunting. However, studies also showed that stunting can be found in wealthy families. To analyze factors related to stunting among wealthy families, we examined the 2021 Indonesian National Nutritional Status Survey. This cross-sectional study included 23,957 children under the age of two years old. In addition to stature, the study analyzed eight independent variables (e.g., residence, maternal age, marital, education, employment, children’s age, gender, and early initiation breastfeeding). By employing a binary logistic regression test in the last analysis, this study found that children in rural areas were 1.160 times more likely to be stunted than those in urban areas (95% CI [1.152, 1.168], p < .001). The characteristics of mothers were also found to be related to stunting, including age, marital status, education, and employment. Additionally, 12–13-month-old children were 3.033 times more likely to be stunted than < 12 months (95% CI [3.011, 3.055], p < .001). Boys were 1.320 times more likely to be stunted than girls (95% CI [1.311, 1.328], p < .001). Children with early breastfeeding initiation were 1.025 times more likely to be stunted than those without (95% CI [1.018, 1.031], p < .001). Lastly, eight significant factors related to stunting among wealthy families in Indonesia were found: residence, maternal age, marital, education, employment, children’s age, gender, and early breastfeeding initiation. The government must focus on the specific targets produced in this study to accelerate reducing the prevalence of stunting in wealthy Indonesian families.